Thapsigargin induces apoptosis in adrenocortical carcinoma by activating endoplasmic reticulum stress and the JNK signaling pathway: an in vitro and in vivo study - Wu L; Huang X; Kuang Y; Xing Z; Deng X; Luo Z (Dove Medical Press, 2019)
Lili Wu,1 Xuemei Huang,2 Yaqi Kuang,2 Zengmiao Xing,2 Xiujun Deng,2 Zuojie Luo21Department of Integrated Medicine, The Affiliated Tumor Hospital of Guangxi Medical University, Nanning, Guangxi 530021, People’s Republic of China; 2Department of Endocrinology, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi 530021, People’s Republic of ChinaObjective: Thapsigargin (TG) is a natural product that exists in most parts of the plant Thapsia garganica L. and possesses potential anticancer activities against variety tumor cell lines. TG induces endoplasmic reticulum (ER) stress and apoptosis by inhibiting cancer growth. However, the antineoplastic effect of TG in human adrenocortical carcinoma (ACC) cells is still unknown.Methods: In this study, two human ACC cell lines including SW-13 and NCI-H295R were employed to explore the potential role of TG in ACC. A mouse xenograft model of SW-13 cells was established to verify the role of TG in vivo. The cell viability was tested using Cell Counting Kit-8 and Transwell assays. Flow cytometry and Hoechst 33,258 staining were employed to analyze cell apoptosis. RT-qPCR and Western blot (WB) were performed to explore the underlying mechanism of TG-induced apoptosis in ACC cells.Results: The results indicated that TG dose-dependently inhibited proliferation, migration and invasion in human ACC cells. TG significantly increased the mitochondrial rate of apoptosis and ER stress activity in ACC cells and suppressed ACC xenograft growth in vivo. In addition, the expression of Jun N-terminal kinase (JNK) signaling-related genes and proteins was upregulated by the treatment with TG.Conclusion: Our findings suggest that TG inhibits the viability of ACC cells by inducing apoptosis through the activation of JNK signaling. Thus, TG is expected to be a potential candidate for the treatment of ACC.Keywords: thapsigargin, adrenocortical carcinoma, apoptosis, Jun N-terminal kinase signaling, endoplasmic reticulum ER stress